Fe and Cu concentration in gills, muscles and gonad of Notopterusnotopterus from the downstream of the Sail River, Pekanbaru - Bangun, Sri Nefrbina; Budijono, Budijono; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract             Sail river has been polluted by heavy metals and those affects the organs of Notopterusnotopterus. To understand the content of Fe and Cu in the gills, muscles, and gonad of the fish, a study has been conducted on December 2017 to January 2018. Samplings were conducted two times, once/month, in the downstream of the river. Heavy metals content were analysedusing AAS.Results shown that the average concentration of Fe in gills, muscles and gonads were 2.123, 1.970 dan 1.095mg/kg, while those of the Cu were1.620, 1,585 dan 0,330mg/kg respectively.Fe and Cu concentration in the fish from the downstream of the Sail River were relativy high Keywords:iron, copper, aquatic organisms, fish organ